Perlindungan Hukum pada Debitur atas Penarikan Objek Jaminan Fidusia melalui Parate Eksekusi - Junaedi, Budi; Tjoanda, Merry; Berlianty, Teng (PATTIMURA Legal Journal, 2022)
Introduction: The arrangement for the execution of fiduciary guarantees as explained in the decision of the Constitutional Court Number 2/PUU-XIX/2021 requires the execution of a fiduciary guarantee certificate which is carried out and applies the same as the execution of court decisions which have permanent legal force. Purposes of the Research: This study aims to find out how the procedure for withdrawing fiduciary guarantees is through the execution parate, and what forms of legal protection are given to debtors for the withdrawal of fiduciary guarantees through the execution parate. Methods of the Research: This study uses a normative legal research method, which aims to determine the procedure for withdrawing fiduciary guarantees through the execution parate, and how the form of legal protection is given to debtors for the withdrawal of fiduciary guarantees through the execution parate. Results Originality of the Research: Legal protection for debtors for the withdrawal of the object of fiduciary security is strengthened through the decision of the Constitutional Court Number 2/PUU-X1X/2021. The decision regulates the existence of an agreement or voluntary surrender of the object of fiduciary security from the debtor to the creditor without any act of unilateral control of the object of guarantee by the creditor. On the other hand, if there is no agreement or voluntary surrender, then new control can be carried out with the knowledge of the court